Encaminhamento de crianças com queixas de leitura e escrita: posição dos familiares - Mazzarotto, Ingrid Helena Elizabeth Kolb (2015)
Children whose academic performance is below the standard rates of reading and writing appropriation have been repeatedly addressed by educators for clinical evaluation services. This study aimed to analyze the perception of family members of the children with alleged difficulties about this routing and the school complaints. It is an exploratory research approved by the Research Ethics Committees (447.163/2013). Participated in the study thirty families of children referred for psychologist, speech therapist and psychopedagogist. Data were collected through semi-structured interviews and analyzed quantitatively and qualitatively. The sample included 28 mothers, a grandmother and a father, aged between 25 and 68 years. The school problems were related to: writing (34%), reading (28%), cognitive aspects (18%), low academic performance (13%) and psychological aspects (6%). It proved to be the prevailing understanding that the appropriation of written language depends on its formal aspects to the detriment of discursive aspects. All respondents agreed with the routing and indicated the tendency to explain the difficulties pointed based on child´s aspects (44%) and family (22%). About the effects of the routing, 68% reported negative impacts on child and on relatives and 53% affirmed they had changed their practices related to reading and writing in the family context.This analysis shows the importance of rethinking the child´s routing practice as a resource enabling active and responsive participation of all stakeholders, facilitating the understanding of written language as a discursive activity.